2000
DOI: 10.1677/jme.0.0240083
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate/retinoic acid costimulation induces apoptosis-independent growth arrest and cell differentiation in normal and ras-transformed seminal vesicle epithelial cells unresponsive to retinoic acid

Abstract: Retinoic acid (RA) and sodium butyrate (NaB) are regulators of cell growth and differentiation. We studied their effect on normal (SVC1) or v-Ki-rastransformed (Ki-SVC1) rat seminal vesicle (SV) epithelial cell lines. The treatment of these cells with 10 7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…1998; Tucholski et al . 2001) or rat epithelial SVC1 (Buommino et al . 2000) cells does not induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1998; Tucholski et al . 2001) or rat epithelial SVC1 (Buommino et al . 2000) cells does not induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…1997), differentiation (Aeschlimann et al . 1993; Buommino et al . 2000), wound healing (Haroon et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were lysed using 0·2% sodium dodecyl sulphate (SDS), 100 µg mL −1 RNase in TNE buffer [150 mmol L −1 sodium chloride, 10 mmol L −1 ethylenediamine tetraacetic acid (EDTA), 10 mmol L −1 Tris–HCl, pH 8], and 100 µg mL −1 of proteinase K were added to the lysate for 2·5 h at 56 °C. The high molecular weight genomic DNA, extracted from proteinase K‐treated lysates, 29 was analysed by electrophoresis in ethidium bromide‐containing 1% agarose gel in TBE (0·045 mol L −1 Tris‐borate, 0·001 mol L −1 EDTA, pH 8·0).…”
Section: Dna Fragmentation Assaymentioning
confidence: 99%
“…In several studies, the life-extending capacity was also shown for sodium butyrate (SB), a short chain fatty acid having HDAC inhibition activity and known to markedly influence the processes of cell growth, differentiation and apoptosis in both normal and transformed cells (Buommino et al 2000;Khan and Jena 2014). The epigenetic modifications potentially involved in the SB-induced life extension in Drosophila have been deeply studied in a series of experiments of the research group headed by Bai-Qu Huang in the Northeast Normal University, Changchun, China (see Table 11.3).…”
Section: Sodium Butyratementioning
confidence: 99%